Hydrogel-inorganic filler composites for 3D bioprinting - Bider, Faina; Boccaccini, Aldo R. (Elsevier, 2023)
Three-dimensional (3D) bioprinting technologies provide opportunities to create cell-laden complex scaffolds for tissue engineering. Hydrogels are the materials of choice for 3D bioprinting applications due to their capability to encapsulate cells in a water-rich environment. Their structure is similar to the one of the natural extracellular matrix. However, standard hydrogels possess usually low mechanical properties and lack adequate functionalities, which can be overcome through the development of multimaterial systems, for example, by incorporation of inorganic fillers. Addition of inorganic fillers, such as hydroxyapatite, nanoclays, bioactive glass (nano)particles and carbonaceous nanomaterials usually results in improved printability of 3D scaffolds due to the possibility to adjust the viscosity and to enhance the mechanical properties of the composite hydrogels. In addition, inorganic fillers provide novel biological functionalities to the hydrogel matrix. The following book chapter gives an outline of the combinations of hydrogels with inorganic fillers, both biodegradable and persistent fillers, including also anisotropic fillers, which are being developed for 13D-bioprinting applications.
CRIS-Team Scopus Importer:2023-11-24
Keywords: 3D bioprinting; bioactive glasses; biofabrication; bioinks; composites; Hydrogels; inorganic filler